2000
DOI: 10.1128/iai.68.8.4498-4504.2000
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the Pseudomonas aeruginosa tonB Gene for High-Affinity Iron Acquisition and Infection

Abstract: To investigate the contribution of the TonB protein to high-affinity iron acquisition in Pseudomonas aeruginosa, we constructed tonB-inactivated mutants from strain PAO1 and its derivative deficient in producing the siderophores pyoverdin and pyochelin. The tonB mutants could not grow in a free-iron-restricted medium prepared by apotransferrin addition, even though the medium was supplemented with each purified siderophore or with a heme source (hemoglobin or hemin). The tonB inactivation was shown to make P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 45 publications
4
65
1
2
Order By: Relevance
“…Indeed, inactivation of iron acquisition systems in S. aureus and many other bacteria can have a detrimental effect on virulence (3,9,14,18,24,30,38,(45)(46)(47)51), while the loss of some iron acquisition functions in some bacteria does not seem to affect virulence, probably due to redundancy of acquisition systems (29,38). For S. aureus, previous studies have demonstrated the importance of siderophore production for full virulence of the organism in a mouse model of infection (14), and Skaar et al have recently shown that heme acquisition by this bacterium is also important for virulence in mice (44).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, inactivation of iron acquisition systems in S. aureus and many other bacteria can have a detrimental effect on virulence (3,9,14,18,24,30,38,(45)(46)(47)51), while the loss of some iron acquisition functions in some bacteria does not seem to affect virulence, probably due to redundancy of acquisition systems (29,38). For S. aureus, previous studies have demonstrated the importance of siderophore production for full virulence of the organism in a mouse model of infection (14), and Skaar et al have recently shown that heme acquisition by this bacterium is also important for virulence in mice (44).…”
Section: Discussionmentioning
confidence: 99%
“…Three TonB homologues, TonB1, TonB2 and TonB3, have been identified in the P. aeruginosa genome sequence and all three homologues have been experimentally characterized Takase et al, 2000;Zhao & Poole, 2000Huang et al, 2004). Siderophore-mediated iron transport in P. aeruginosa is primarily dependent on the activity of the TonB1 protein.…”
Section: Activity Analysis Of Chtamentioning
confidence: 99%
“…The P. aeruginosa genome contains many homologues of iron-siderophore receptor genes, reflecting the enormous flexibility of this organism to use various iron carriers. The ability to use such a wide variety of siderophores underscores the importance of iron for bacterial growth and survival as well as the need to compete with other microorganisms within the environments they inhabit for this essential metal (21,22).…”
Section: -(1-hydroxydecylidene)-5-(2-hydroxyethyl)pyrrolidine-24-dimentioning
confidence: 99%